Antimicrobial and toxicological evaluation of the leaves of Baissea axillaries Hua used in the management of HIV/AIDS patients - Agoreyo Freddy O; Abere Tavs A (BMC, 2006)
Abstract Background Persistent diarrhea is a common endemic disease with high incidence among the Africans including Nigerians. It also represents a frequent opportunistic disease in people living with HIV. Diarrhea represents one of the most distressful and persistent symptoms of HIV/AIDS, which may or may not be accompanied by an infection. The leaves decoction of Baissea axillaries Hua (Apocynaceae) is used by traditional herbalists in Edo state, Nigeria for the management of people living with HIV/AIDS. Determination of its antimicrobial activity and toxicological profile will provide supportive scientific evidence in favour of its continuous usage. Method Chemical and chromatographic tests were employed in phytochemical investigations. Inhibitory activities of aqueous and ethanolic extracts against clinical strains of Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Streptococcus faecalis were compared with Togamycin (Spectinomycin). Our report includes minimum inhibitory concentration (MIC) against the test organisms. Toxicological evaluation was determined by administering 250 mg/kg and 500 mg/kg of extracts on male Wister rats for 14 days with normal saline as control. The kidneys, liver, heart and testis tissues were examined. Results Phytochemical studies revealed the presence of alkaloids, tannins, and cyanogenetic glycosides. The extracts inhibited the growth of Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus to varying extents, but only the ethanolic extract inhibited growth in Streptococcus faecalis. The LD50 of the extract in mice was above 5000 mg/kg body weight when administered intraperitoneally. Toxicological evaluation showed mere ballooning degeneration of the liver at 250 mg/kg while at 500 mg/kg there was tissue necrosis. The low and high doses showed ill-defined leydig cells in the testis and no remarkable changes in the heart and kidneys. Conclusion Extracts of Baissea axillaries have demonstrated antimicrobial activity against clinical strains of selected microorganisms. While there is toxicity at the dose of 500 mg/kg, the therapy shows potential for application in the treatment of diarrhoea associated with AIDS/HIV. Further studies of Baissea axillaries on diarrhoea and toxicity are necessary to evaluate its mechanism of action and to fully establish its safety profile.